Electing to Play: MTV's Fantasy Election and Changes in Political Engagement Through Gameplay. (November 2014) - Foxman, Maxwell; Forelle, Michelle
In 2012, MTV explored a new approach to voter engagement through "Fantasy Election." The game had players draft candidates in the congressional and presidential elections onto personal teams in order to compete for points and prizes, which were distributed based not only on the candidates' actions but also when players themselves took action to become better informed and involved during the campaign. In the end, Fantasy Election drew over 10, 000 active participants. This article scrutinizes the design and effect of the game by using data from MTV's exit survey of Fantasy Election users to explore whether and how games can be used to encourage voter engagement. By considering the self-reported motivations of players, and a broader discussion of the role of play, competition and reward in fostering political and civic participation, we consider how gamification strategies have ambivalent effects on developing a more informed and cooperative civil society.